An investigation into whether cardiac risk stratification protocols actually predict complications in cardiac rehabilitation programs? - Ribeiro, Felipe [UNESP]; Takahashi, Carolina [UNESP]; Vanzella, Lais Manata [UNESP]; Laurino, Maria Julia Lopez [UNESP]; Lima, Isabelle Maina [UNESP]; Silva, Vitor Eduardo dos Santos [UNESP]; Silva, João Pedro Lucas Neves [UNESP]; Valente, Heloisa Balotari [UNESP]; da Silva, Anne Kastelianne França [UNESP]; Christofaro, Diego Giulliano Destro [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP] (SAGE Publications, 2021)
Objectives: This study evaluated the capacity of cardiac risk stratification protocols on simple complications that occur during activities of a cardiovascular rehabilitation program. Design: Observational longitudinal cohort study. Setting: Outpatient clinic of cardiovascular rehabilitation. Subject: Patients diagnosed with cardiovascular disease and/or risk factors. Interventions: Not applicable. Main measures: The relationship between the cardiac risk classes of seven risk stratification protocols and the occurrence of simple complications (such angina, abnormal changes in blood pressure, arrhythmias, fatigue, muscle pain, pallor) was assessed using the chi-square test, and when statistical significance was observed, sensitivity, specificity and accuracy were determined. Results: About 76 patients were analyzed. The American Association of Cardiovascular and Pulmonary Rehabilitation (AACVPR) protocol showed a statistically significant relationship between simple complications and cardiac risk classes (P-value = 0.046), however the results of sensitivity (0.53), specificity (0.52), and accuracy (0.53) were not significant. The other protocols analyzed were not significant: American College of Sports Medicine (P-value = 0.801), Brazilian Society of Cardiology (P-value = 0.734), American Heart Association (P-value = 0.957), Pashkow (P-value = 0.790), Society French Cardiology (P-value = 0.314), and Spanish Society of Cardiology (P-value = 0.078). Conclusion: The AACVPR protocol showed a significant relationship between the risk classes and the occurrence of simple complications, however, the low values obtained for sensitivity, specificity and accuracy show that it is not useful for this purpose. Clinical trials registration: NCT03446742.
Keywords: cardiac events; Cardiac rehabilitation; cardiac risk; clinical protocols; signals and symptoms